Maternal caffeine consumption and childhood behavioural and neurocognitive development: A focused narrative review - James, Jack E (Archives of Community Medicine and Public Health, 2021)
Rationale: The majority of pregnant women regularly consume caffeine, a habit-forming substance of no nutritional value for mother or baby. Objectives: To examine evidence of association between maternal caffeine consumption and childhood behavioural and neurocognitive development, and to consider the soundness of current health guidance concerning the consumption of caffeine during pregnancy. Methods: Database searches identified a large pool of peer-reviewed articles, which when culled for relevance yielded a modest corpus of animal and human research for inclusion in this focussed narrative review of potential caffeine-related threats to childhood behavioural and neurocognitive development. Results: High biological plausibility of potential harm from maternal caffeine exposure indicated by early animal research is confirmed by more recent animal studies that sought to mimic human consumption patterns. Reported negative outcomes include increased neuronal network excitability and susceptibility to seizures in offspring, and disruptions to electrophysiological activity, learning, and memory. In contrast, human observational studies have yielded inconsistent findings. Some studies have reported evidence of negative behavioural and neurocognitive outcomes, including hyperkinetic disorder, attention deficit disorder, and intelligence level in preschool- and elementary-aged children. Other studies, however, reported no associations with maternal caffeine consumption for similar parameters. Conclusions: Current understanding of caffeine-related increased risk of harm for childhood development is limited due to inconsistent findings from human research. However, persistent reports of possible negative outcomes indicate high priority need for further research. In the meantime, the cumulative scientific evidence supports advice to pregnant women and women contemplating pregnancy to avoid caffeine.